Woods Charred at Low Temperatures and Their Modification for the Adsorption of Cr(VI) Ions from Aqueous Solution - Zhenze Li; Takeshi Katsumi; Toru Inui; Shigeyoshi Imaizumi (Adsorption Science & Technology)
Despite being prepared at higher temperatures and involving greater energy consumption, activated carbons always show a smaller capacity and affinity towards the adsorption of Cr(VI) ions. After a brief review regarding Cr(VI) ion contamination and treatment, the preparation of a novel biosorbent from pyrolyzed wood char for Cr(VI) ion adsorption is described. Pyrolysis was conducted at temperatures within the range 200–350 °C, thereby helping to protect beneficial functional groups, saving energy and hence reducing costs. The influence of pH, concentration, adsorbent dosage, ionic strength and equilibration time on Cr(VI) ion adsorption by this biosorbent was investigated. It was shown that the char obtained at 200 °C possessed the highest Cr(VI) ion retention capacity (31.96 mg/g) but required the longest equilibration time (> 47 d). Coating the char with nano-scale iron oxide greatly improved its adsorption affinity towards Cr(VI) ions, with a higher adsorption affinity (Henry's law K d = 2.988 ℓ/mg) and an enhanced Cr(VI) ion adsorption capacity (53.45 mg/g) being accomplished within a much shorter equilibration time (24 h). Spectroscopic studies confirmed that complexation of Cr(VI) ions occurred via surface hydroxy groups. The methods proposed for preparing and modifying wood char are likely to be applicable in industrial wastewater treatment.